Hybrid legged-wheeled robot path following: a realistic simulation approach - Pinto, Vítor H. (2022)
Legged-wheeled locomotion systems are particular cases used for robots, increasing their degrees of freedom. To increase safety and robustness in the performance of industrial robots, by decreasing the chance to easily break their joints or hurt someone, the use of non-rigid joints is being increasingly found in the literature and in the industry. Realistic simulators are tools capable of detecting rigid bodies interactions through physics engines. This paper present the simulation model of a hybrid legged-wheeled robot, built in the SimTwo simulator. Later, the proposed algorithms for path following control were detailed. Several tests were performed to the implemented path following algorithms. These showed that the errors in linear paths are at most 1 cm. For circle paths, the maximum error is 3 cm.